2017
DOI: 10.1371/journal.pone.0179266
|View full text |Cite
|
Sign up to set email alerts
|

Elevated C-reactive protein level during clinical remission can predict poor outcomes in patients with Crohn’s disease

Abstract: Intestinal inflammation and mucosal damage in Crohn’s disease (CD) are believed to progress even during clinical remission. We investigated the long-term prognosis of CD patients in clinical remission according to serum C-reactive protein (CRP) levels. This study included 339 CD patients in clinical remission (Crohn’s disease activity index < 150) for more than 6 months between January 2008 and December 2010. Clinical outcomes were compared between patients with normal and elevated CRP levels during clinical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…Additionally, when comparing active and inactive IBD cohorts reporting little to no pain, we found that several inflammatory markers (including WBC, platelet count, ESR and CRP) may be elevated in hypoalgesic IBD, supporting the findings of previous studies [8,25]. However, a quarter or more of these patients will demonstrate normal inflammatory markers, demonstrating the potential limitation of this type of testing.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Additionally, when comparing active and inactive IBD cohorts reporting little to no pain, we found that several inflammatory markers (including WBC, platelet count, ESR and CRP) may be elevated in hypoalgesic IBD, supporting the findings of previous studies [8,25]. However, a quarter or more of these patients will demonstrate normal inflammatory markers, demonstrating the potential limitation of this type of testing.…”
Section: Discussionsupporting
confidence: 85%
“…Several endoscopic, radiologic and laboratory tests have been proposed as screening options for silent IBD [11,[21][22][23][24][25], but their clinical practicality and cost-effectiveness are still uncertain, particularly when the scale of this issue remains incompletely understood. To this point, no studies have specifically evaluated for reduced abdominal pain perception in IBD patients while simultaneously evaluating disease activity using the most reliable assessment methods (e.g., direct endoscopic visualization).…”
Section: Introductionmentioning
confidence: 99%
“…According to previous research, increased CRP in adult patients with CD increases the risk of CD-related hospitalization and CD-related intestinal resection. CRP levels >1 mg/dL have been found to be correlated with granulomatous CD in pediatric patients in the United States [ 26 27 28 29 ]. In the present study, we found that ESR and CRP significantly increased in the presence of upper GI symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…C‐reactive protein (CRP) is routinely used in the diagnosis for monitoring infections especially in the obstetric field 36,37 . CRP is also an important biomarker for predicting long‐term outcome in inflammatory disease 38 . Carbone et al 29 showed that maternal serum levels of CRP during the second trimester of pregnancy represent a useful predictor of maternal adverse outcome occurrence.…”
Section: Discussionmentioning
confidence: 99%